Do Income Level and Gender Diversity Influence Tax Literacy? Evidence from Small and Medium Enterprises in Uzbekistan - Baratova Charoskhon Dilmurodovna; R Nelly Nur Apandi; Zulayho Umarova (Tazkia Islamic University College, 2026)
This study examines the determinants of tax literacy among Micro, Small, and Medium Enterprise (MSME) entrepreneurs in Uzbekistan, focusing specifically on the influence of income levels and gender diversity. While tax literacy is a critical precursor to voluntary tax compliance, empirical evidence remains sparse within the context of Central Asian transition economies. Adopting a quantitative research design, primary data were gathered from 40 MSME practitioners via structured instrumentation and subsequently subjected to multiple regression analysis. The empirical results demonstrate that income level exerts a statistically significant positive effect on tax literacy, indicating that higher economic capacity correlates with a more sophisticated understanding of fiscal obligations and regulatory procedures. Conversely, gender diversity was found to have no significant impact on tax literacy, nor did it function as a moderator in the relationship between income and tax knowledge. These findings suggest that in the Uzbekistani MSME landscape, structural economic factors outweigh demographic variables in shaping financial and fiscal competence. The study concludes that to enhance systemic voluntary compliance, policymakers should implement stratified tax education initiatives tailored to different income cohorts, thereby fostering a more robust and equitable fiscal ecosystem.